Impella removal with access site salvage. Issue 1 (26th February 2018) - Yager, Neil; Waxman, Sergio
Abstract: Removal of the percutaneous Impella CP assist device while maintaining femoral artery access site is not always possible. This case highlights a technique of Impella removal with access site salvage.